(untitled) (KMC Journal, 2023)
This study explores the perception of teachers towards English medium instruction (EMI) along with the challenges in implementing EMI in public schools of Nepal. Adopting phenomenological qualitative research design, three secondary level English language teachers from three community schools of Kailali district running EMI up to secondary level were purposively selected as research participants. A semi-structured interview (30 minutes each) was undertaken with the participants to collect information. The study reveals that even though teachers have positive attitudes toward EMI, they are still facing difficulty in implementing EMI successfully in the schools. The research participants perceive some challenges such as lack of competence in English, uncertain roles and responsibilities of teachers, lack of teacher training or workshop, lack of authentic resources and instructional materials, lack of infrastructure, students’ motivation towards learning and lack of awareness of the parents. Similarly, the study also reveals that the schools are unable to implement EMI effectively because of a lack of clear government policy, lack of effective supervision mechanism and inadequate support from the government and community.